Safety and efficacy of 48 mm Xience Xpedition everolimus‐eluting stent for the treatment of long coronary lesions. Issue 2 (27th May 2022) - Gautier, Alexandre; Hovasse, Thomas; Arroyo, Diego; Unterseeh, Thierry; Garot, Philippe; Champagne, Stéphane; Neylon, Antoinette; Sanguineti, Francesca; Benamer, Hakim; Chevalier, Bernard; Lefèvre, Thierry
Abstract: Introduction: Long drug‐eluting stents may limit the issue of overlapping multiple stents when treating long coronary lesions. Aim: The aim of the study was to assess the safety and efficacy of the 48 mm Xience Xpedition everolimus‐eluting stent (48mm‐EES) for the treatment of long coronary lesions, in an all‐comer population. Methods: Patients receiving at least one 48mm‐EES were prospectively included from March 2014 to December 2018. The primary endpoint was target lesion failure (TLF), defined as a composite of cardiac death, target vessel myocardial infarction, and clinically driven target lesion revascularization (TLR) at 1 year. The main secondary endpoint was the patient‐oriented composite endpoint (POCE) defined as a composite of death, stroke, myocardial infarction, and reintervention. Results: A total of 268 patients with 276 long coronary lesions, including 94 chronic total occlusions (CTO), were successfully treated using at least one 48mm‐EES. The total stent length per lesion was 66 ± 22 mm. A single 48mm‐EES was suitable to successfully treat the target lesion in 48% of cases (60% for non‐CTO lesions). One‐year follow‐up rate was 96.3%. TLF occurred in 13 patients (5.3%), mainly driven by TLR (4.1%). Two cardiac death occurred (0.7%). POCE occurred in 30 patients (11.6%) mainly driven by repeat revascularization (9.7%). Definite stent thrombosis was observed in two patients (0.7%). No difference was observed in one‐year outcomes between single 48mm‐EES and multiple stents implantation as well as between CTO and non‐CTO lesions. Conclusion: The 48mm‐EES is safe and effective to treat long coronary lesions, including CTOs, and provides attractive cost‐effectiveness by limiting multiple stenting.